Changing styles of informal academic communication in the age of the web: Orthodox, moderate and heterodox responses. Issue 5 (24th July 2017) - Shehata, Ahmed; Ellis, David; Foster, Allen Edward
Abstract : Purpose: The purpose of this paper is to report the findings of a study to investigate the changes in scholarly communication practices among a group of scholars in the UK and build upon the results that were published in a previous paper. Design/methodology/approach: The study deployed a naturalistic inquiry approach using semi-structured interviews as a qualitative research tool. A sample of 40 participants from four UK universities was interviewed to explore the changes in informal scholarly communication behaviour. Findings: The analysis of the interviews revealed that there are three ideal types of behaviour: the "orthodox" uses formal and traditional scholarly communication approaches; the "moderate" prioritises formal communication approaches, but at the same time is trying to get benefits from informal channels; and, the "Heterodox" uses all channels available in the scholarly communication. Originality/value: The value of the current study lies in using a naturalistic inquiry approach to investigate the changes in scholarly communication practices, and to explore the different scholarly communication styles. In the context of this study, the use of a naturalistic approach and grounded theory principles in connection with coding provided a stance that allows for the gathering of rich information to enable understanding and explanation of scholarly communication activities in addition to uncovering themes that related to scholarly behaviour.